Corrosion effect to the surface of stainless steel treated by two processes of low temperature carburization1. (18th March 2014) - Balijepalli, S. K.; Ceschini, L.; Chiavari, C.; Kaciulis, S.; Martini, C.; Mezzi, A.; Montanari, R.; Verona Rinati, G.; Abel, Marie‐Laure; Rossi, Antonella; Watts, John F.
<x xml:space="preserve">Abstract</x> AISI 316L austenitic stainless steel is widely used in industrial applications, usually in contact with corrosive environments. Low temperature carburization (LTC) is a treatment increasingly applied to these steels in order to harden the surface without decreasing the corrosion resistance.In the present work, LTC techniques such as industrial and plasma‐assisted treatments were applied to stainless steel and compared for their resistance to corrosion. The micro‐chemical composition of hardened layer before and after corrosion treatments was studied on both the samples by surface‐sensitive XPS and AES techniques. The results of plasma‐assisted LTC treatment showed similar behavior of corrosion resistance as industrial LTC treatment. Hence, the plasma‐assisted LTC treatment can be a suitable replacement for the industrial LTC treatment of stainless steels Copyright © 2014 John Wiley & Sons, Ltd.